2019
DOI: 10.4049/immunohorizons.1800015
|View full text |Cite
|
Sign up to set email alerts
|

B Cell–Mediated Antigen Presentation through MHC Class II Is Dispensable for Atherosclerosis Progression

Abstract: Depletion of B cells attenuates plaque development and modulates T cell responses in mouse models of atherosclerosis, suggesting that Ag presentation by B cells may promote disease progression. Thus, we set out to determine the role of B cell-mediated MHC class II (MHC II) Ag presentation during atherosclerotic plaque development. We developed murine conditional MHC II deletion and expression systems under control of the B cell-restricted CD19 promoter in an experimental model of atherosclerosis. Mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our observation is in accordance with reports where anti-CD40 antibody treatment reduced atherosclerosis in LDLR −/− mice (72) and inhibition of Th1 responses reduced atherosclerosis in ApoE −/− mice (73). Recently, Wigren et al, and Williams et al, reported that global or B cell-specific deficiency of MHCII were associated with low level of total IgG and IgM as well as low or undetectable oxLDL specific antibodies (74,75), supporting our data by defining differential roles of a B cell-specific MHCII and CD40 in generation of plasma cells and antibodies. Interestingly, in contrast to increased atherosclerosis in MHCII −/− ApoE −/− double knockout mice (74), MHCII deficiency on B cells did not affect atherosclerosis in LDLR −/− mice despite large but incomplete reductions in MHCII in B cells (75); reductions resulted in reduced IgG1 and IgG2c but not IgG2b nor IgM.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our observation is in accordance with reports where anti-CD40 antibody treatment reduced atherosclerosis in LDLR −/− mice (72) and inhibition of Th1 responses reduced atherosclerosis in ApoE −/− mice (73). Recently, Wigren et al, and Williams et al, reported that global or B cell-specific deficiency of MHCII were associated with low level of total IgG and IgM as well as low or undetectable oxLDL specific antibodies (74,75), supporting our data by defining differential roles of a B cell-specific MHCII and CD40 in generation of plasma cells and antibodies. Interestingly, in contrast to increased atherosclerosis in MHCII −/− ApoE −/− double knockout mice (74), MHCII deficiency on B cells did not affect atherosclerosis in LDLR −/− mice despite large but incomplete reductions in MHCII in B cells (75); reductions resulted in reduced IgG1 and IgG2c but not IgG2b nor IgM.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Wigren et al, and Williams et al, reported that global or B cell-specific deficiency of MHCII were associated with low level of total IgG and IgM as well as low or undetectable oxLDL specific antibodies (74,75), supporting our data by defining differential roles of a B cell-specific MHCII and CD40 in generation of plasma cells and antibodies. Interestingly, in contrast to increased atherosclerosis in MHCII −/− ApoE −/− double knockout mice (74), MHCII deficiency on B cells did not affect atherosclerosis in LDLR −/− mice despite large but incomplete reductions in MHCII in B cells (75); reductions resulted in reduced IgG1 and IgG2c but not IgG2b nor IgM. Incomplete depletion of MHCII from B cells is known to lead to strong selection of escaped B cells where MHCII is not deleted in the activated and plasmablast compartments (76,77), which may partially explain the latter observation.…”
Section: Discussionsupporting
confidence: 87%
“…Transfer of WT B cells led to a drastic increase in atherosclerosis due to the infiltration of activated CD4 T cells into atherosclerotic lesions; however, this effect was significantly reduced when MHC-II-deficient B cells were used for adoptive transfer [ 161 ]. In the study from Williams and colleagues, CD19 cre recombinase was used to either delete or overexpress MHC-II specifically in B cells from Ldlr −/− mice [ 162 ]. No difference in atherosclerotic lesion size nor in lesion immune cell content was observed.…”
Section: Antigen Presentation and Co-stimulatory Moleculesmentioning
confidence: 99%
“…Mouse models showed that the depletion of B-cells attenuates plaque development. This suggests that antigen presentation of B-cells can promote atherosclerotic progression [58]. Indeed, differential effects of different B-cell subsets exist.…”
Section: Essential Mechanisms Promoting Vulnerabilitymentioning
confidence: 99%